The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1073/pnas.79.2.542
|View full text |Cite
|
Sign up to set email alerts
|

Mutation frequencies in male mice and the estimation of genetic hazards of radiation in men.

Abstract: Estimation of the genetic hazards of ionizing radiation in men is based largely on the frequency of transmitted specific-locus mutations induced in mouse spermatogonial stem cells at low radiation dose rates. The publication of new data on this subject has permitted a fresh review of all the information available. The data continue to show no discrepancy from the interpretation that, although mutation frequency decreases markedly as dose rate is decreased from 90 to 0.8 R/min (1 R = 2.6x 10' coulombs/kg) there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(56 citation statements)
references
References 18 publications
6
49
1
Order By: Relevance
“…Doubling doses were higher in irradiated premeiotic and meiotic spermatogenic cell types in the present study compared to those reported from other germline mutation assays [43][44][45][46]. Notably, the Lac I mutation reporter system is effective in reporting point mutations, but is not as effective in reporting larger deletions, insertions or rearrangements.…”
Section: Discussioncontrasting
confidence: 70%
“…Doubling doses were higher in irradiated premeiotic and meiotic spermatogenic cell types in the present study compared to those reported from other germline mutation assays [43][44][45][46]. Notably, the Lac I mutation reporter system is effective in reporting point mutations, but is not as effective in reporting larger deletions, insertions or rearrangements.…”
Section: Discussioncontrasting
confidence: 70%
“…While average mutation rates increased by three-to fourfold at the highest radiation dose used, it is of some concern that the variation in mutation rate found between individual mouse families was equally large (three-to fourfold) at a given dose. Similar data were reported for more densely ionizing neutron irradiations; where sufficient data have been reported, the relative effectiveness of fission neu-256 REVIEW Generally, using conventional mutation measurements, the risk of genetic effects of sparsely ionizing radiations for both somatic and germ cells has been found to decrease with reduction of dose rate down to ϳ10 mGy/min, attributable to more effective DNA repair at lower dose rates (72). However, for the induction of ESTR mutation in spermatogonial stem cells, radiation delivered over 100 h at a dose rate of 0.166 mGy/min was found to be as effective as that given at a rate of 0.5 Gy/min (40).…”
Section: Dose Responses Dose-rate Effects and Doubling Dosessupporting
confidence: 55%
“…Despite the very high mutation rate found for ESTR sequences, estimates of the doubling dose (the dose at which the mutation rate is increased to twice the naturally occurring rate) are little different from those found for conventional mutation analyses in mice (72). Thus Dubrova and colleagues estimated the doubling dose to be around 0.5 Gy for pre-meiotic stage irradiation and 0.33 Gy in their later studies (63,68,71).…”
Section: Dose Responses Dose-rate Effects and Doubling Dosesmentioning
confidence: 97%
“…However, the data from animal models have clearly demonstrated that effects of the parental radiation exposure are transmitted through the germline to the progeny of the irradiated parent [Morgan, 2003a,b,c]. Early studies of these transgeneration effects used various tests such as the specific locus, dominant lethal, and heritable translocation assays [Generoso et al, 1980;Russell and Kelly, 1982;Green et al, 1987;Russell et al, 1998]. Other studies focused on heritable alterations in cancer incidence and teratogenesis following the parental preconception irradiation [Mohr et al, 1999;Pils et al, 1999;Nomura, 2003;Nomura et al, 2004;Dasenbrock et al, 2005].…”
Section: Transgeneration Radiation-induced Effectsmentioning
confidence: 99%